Geographical, anthropogenic and climatic determinants of bryophyte species composition and richness in the Shengsi archipelago, East China Sea. (3rd April 2019) - Yu, Jing; Shen, Lin; Zang, Cheng; Cai, Jinrong; Guo, Shuiliang
ABSTRACT: Introduction. Few attempts have been made to assess the comparative contributions of different environmental factors on species composition (SC) and richness (SR) of bryophytes on continental islands. Methods. The bryophyte flora and the impact of seven environmental variables (island area, elevation, isolation, human disturbance, rainfall, vegetation cover, and exposed rock area) on 18 continental islands of the Shengsi archipelago in the East China Sea were investigated. Redundancy Analysis and Canonical Correspondence Analysis were used to determine to what extent the environmental variables could explain variation in species richness and species composition on these islands. Key results & Conclusions. Island elevation, isolation, area and human disturbance intensity all significantly influenced bryophyte SC at island level, accounting for 12.7%, 9.9%, 8.8% and 7.8% of the total SC variation, respectively. Island area was the most important determinant of bryophyte SR ( P = 0.002), accounting for 58.3% of the total variation (9.7% by area per se and 48.6% confounded with other variables); elevation and human disturbance intensity also significantly influenced species richness, accounting for 10.5% and 6.9% of the total SR variation (conditional effects), respectively. Elevation and area had a positive interaction effect on SR while isolation exerted no significant effects ( P > 0.05). The relationships of bryophyte species number (S) with area (A) follow log10 (S) = c + z × log10 (A), with z values from 0.28 to 0.38. The effects of human disturbance on bryophyte SR followed the Gaussian model, supporting the 'intermediate disturbance hypothesis' to some extent.